Hubungan Kebiasaan Konsumsi Fast Food dengan Status Gizi pada Remaja di SMAN 8 Kota Jambi - Amanda, Della Amelia; Wulansari, Arnati; Indrawati, Iin (Jurnal Akademika Baiturrahim Jambi, 2025)
Fast food is a type of food that is can be prepared in a simple way. The impact that can arise from the consumption of fast food is an increase in cholesterol levels, coronary heart disease, diabetes mellitus, and can affect nutritional status. The purpose of this study was to determine the relationship between fast food consumption habits and nutritional status. This study used a cross sectional design. The number of respondents was 70 people by filling out the FFQ questionnaire. The sampling technique used is purposive sampling. The data analysis used was univariate and bivariate analysis using a correlation test with a significance level of alpha 5 (0.05). The results showed that as many as 31.4% of respondents often consumed fast food and as many as 45.7% of respondents experienced excess nutrition. The results of the correlation test between the frequency of fast food consumption and nutritional status showed a p-value of 0.000 <0.05 which stated that there was a significant relationship between fast food consumption habits and nutritional status. This study can be concluded that the more often a person consumes fast food, it will affect their nutritional status.